2020
DOI: 10.4049/jimmunol.204.supp.140.12
|View full text |Cite
|
Sign up to set email alerts
|

Butyrophilin molecules govern γδ T cell reactivity against phosphoantigens

Abstract: Humans have a minor lymphocyte population of gamma-delta (γδ) T cells. The majority of these express a recombined Vγ9Vδ2 T cell receptor (TCR) attractive to immunotherapy. This distinct TCR conveys reactivity to phosphorylated antigens (pAg) that derive from pathogens or accumulate inside tumour cells. Such T cell responses are regulated by butyrophilin (BTN) 3A1 and other membrane-related proteins present on antigen-presenting cells. However, the activation mechanism and direct molecular ligand recognised by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…As mentioned above, Vg9Vd2 T cells are the dominant and most studied subset in human peripheral blood. Their semi-invariant TCRs recognize small non-peptide pyrophosphate antigens through conformational changes after BTN2A1 and BTN3A1 heterodimers bind PAgs intracellularly (8,9). Typical natural PAgs include isopentenyl pyrophosphate (IPP) and (E)-4hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP), with the latter being the most potent natural PAg currently known (69).…”
Section: Gd T-cell Immunotherapy In Cancermentioning
confidence: 99%
“…As mentioned above, Vg9Vd2 T cells are the dominant and most studied subset in human peripheral blood. Their semi-invariant TCRs recognize small non-peptide pyrophosphate antigens through conformational changes after BTN2A1 and BTN3A1 heterodimers bind PAgs intracellularly (8,9). Typical natural PAgs include isopentenyl pyrophosphate (IPP) and (E)-4hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP), with the latter being the most potent natural PAg currently known (69).…”
Section: Gd T-cell Immunotherapy In Cancermentioning
confidence: 99%
“…First, we have shown that Vd2+ T-cells in circulation express various activation markers. Vd2+ T-cell recognition has been widely documented to be due to recognition of phosphoantigens via BTN3A1 and the TCR (6)(7)(8). Recognition also occurs via NKG2D and the recognition of stress ligands MICA/B and ULBPs (11,65,66).…”
Section: Discussionmentioning
confidence: 99%
“…This cell population has also been implicated in anti-tumour responses due to their ability to recognise phosphoantigens from dysregulated mevalonate pathways. Full activation occurs via the recruitment of butyrophilin 3A1 (BTN3A1), which together with BTN2A1 engages the T-cell receptor (TCR) (6)(7)(8)(9)(10). In addition to recognising phosphoantigens, Vg9Vd2 T-cells can also recognise upregulated cell stress ligands through expression of various NK associated activatory receptors (11).…”
Section: Introductionmentioning
confidence: 99%
“…This concept is based on the anti-tumor activity of g9d2 T cells, which are important players in the recognition of foreign pathogens, virally infected cells, and also cancer cells (14). Vg9d2 T cells, a specific gdT cell subset mainly found in the blood, recognize members of the butyrophilin (BTN) family, namely BTN2A1, through the gamma chain of their Vg9d2TCR, and additionally require BTN3A1 expression on the tumor cells for full activation (15)(16)(17). Recognition of the BTN2A1-BTN3A1 complex is induced by an intra-cellular accumulation of phosphoantigens (pAg) that can bind to the intracellular B30.2 domain of BTN3A1, which is modulated by RhoB (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Critical for the GAB concept remains the rather low affinity of the Vg9d2 TCR for its ligands, which has been reported in the µM range (15,16), a couple of magnitudes lower than the high affinity antibody derived domains generally used for tumor binding in TCEs. For abTCR based TCEs, like Tebentafusp, the consensus is that affinity maturation of the abTCR from µM to pM is required to create a functional TCE (26).…”
Section: Introductionmentioning
confidence: 99%